Frequency of MCP-1 (rs1024611) and CCR2 (rs1799864) gene polymorphisms and its effect on gene expression level in patients with AgP. (August 2017) - Gunpinar, Sadiye; Alptekin, Nilgun Ozlem; Ucar, V. Betul; Acar, Hasan
Highlights: Frequency of MCP-1 and CCR2 polymorphisms were analyzed in patients with AgP. MCP-1 and CCR2 genotypes were not associated with AgP. Gene expressions of MCP-1 were similar between AgP and H regardless of genotype. MCP-1 genotype did not alter gene expression and GCF levels within AgP subjects. Homozygous "AA" H subjects showed increased MCP-1 gene expression levels. Abstract: Objective: To identify the genetic risk markers of aggressive periodontitis (AgP), researchers focus on genetic components that regulate the immune response. Therefore the purpose of this study was to investigate genetic impact of monocyte chemoattractant protein (MCP)-1–2518 A/G and CC chemokine receptor 2 (CCR2) −190 G/A gene polymorphisms on AgP susceptibility and the effect of this polymorphism on MCP-1 gene expression in patients with AgP. Material and methods: A total of 215 subjects, 108 AgP and 107 periodontally healthy (H) were recruited in this cross-sectional study (NCT02817568) . Gene polymorphisms of MCP-1–2518 A/G and CCR2–190 G/A were analyzed by a standard polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) assay. MCP-1 messenger (m) RNA expression was measured using quantitative real-time (RT)-PCR in peripheral blood leukocytes from 26 AgP and 16 H controls. Threshold cycles (Ct ) values were obtained from the RT-PCR analysis based on SYBR Green detection and data was normalized via ΔCt . Results: There were no differences between AgP and H groups with regard to MCP-1 and CCR2 genotype distribution and allele frequencies (p > 0.05). In contrast, the MCP-1 mRNA expression levels were higher in homozygous "AA" control subjects than having G + genotype and AA homozygous AgP patients. Conclusions: It can be concluded that MCP-1 and CCR2 polymorphisms are not associated with AgP in Turkish population. Although in AgP patients, there was AA genotype with MCP-1 mRNA expression it can be speculated that gene expression levels in peripheral blood may not reflect the cytokine/chemokine levels of local tissues.